Polarization correlations for electron-impact excitation of neon at 50 eV. (29th July 2015) - Hargreaves, L R; Wright, R; Khakoo, M A; Zatsarinny, O; Bartschat, K; Dipti; Srivastava, Rajesh; Stauffer, A D
Abstract: We present measurements and calculations of linear and circular polarization correlations for angle-differential electron-impact excitation of the neon resonance transition at an impact energy of 50 eV, most importantly extended to large scattering angles up to 105°. The measured linear polarization parameters of the vacuum ultra-violet transition are in very good agreement with a number of theoretical predictions at all angles. At intermediate scattering angles, however, the circular polarization parameter measurements are only found to be in excellent agreement with theoretical results obtained with the B -spline R -matrix theory, but not with those from other models.